Baiplabika prekshāpaṭe Kamareḍa Sirāja Sikadāra - Sādeka, Ābu Jāphara Mostaphā (prāptisthāna, Calantikā Baighara, 1981)
On the political philosophy of Sirāja Sikadāra, 1944-1975, founder of Pūrba Bāṃlā Sarbahārā Pārṭi, splinter group of the former East Pakistan Communist Party (Marxist-Leninist)